Prevalence and Determinants of Cigarette Smoking among the College Students of Kathmandu Valley - Aryal, Umesh Raj; Deuba, Keshab; Subedi, Arjun; Shrestha, Rachana; Bhatta, Laxmi (Asian Journal of Medical Sciences, 2011)
Objective: To estimate the prevalence of smoking among the college students and to identify the factors associated with smoking. Material & Methods: This is a cross sectional study carried out on 304 college students in Kathmandu valley using purposive sampling during the months of December 2009 to January 2010. The self administrated questionnaire was adopted from Global Youth Tobacco Survey 2007 (GYTS) and data were collected after the verbal consent taken. The statistical analysis was done using descriptive statistics, univariate and binary logistic regression to measure prevalence of smoking and to identify the association between dependent and independent variables. Results: We found 7 in 10 students were currently smokers. Among currently smokers, 78% were established smokers. The mean age of smoking onset was 14.15 years (SD=2.62). The mean number of cigarettes smoked per day was 5.03(SD=3.72) and average daily expenditure was Rs. 15.18 (SD=7.87). About 90% students tried to quit smoking and 17% non smokers were susceptibility smokers. The following factors: sex (adjusted odds ratio(aor)=3.88,95% CI= 2.12;7.11), living with or without family members (aor=1.79,95% CI=1.01;3.17), father occupation (aor=1.85,95% CI=1.04;3.30), and friend's smoking habits (aor=4.60,95% CI =1.92;11.0) were associated with cigarette smoking. Conclusion: There is the need of effective intervention programs to control cigarette smoking among college students. Key Words: Cigarette smoking; College students; Prevalence of smoking; Risk factors DOI: 10.3126/ajms.v1i2.3279 Asian Journal of Medical Sciences 1 (2010) 53-58